Theoretical Study of Abnormal Thermal Expansion of CuSCN and Effect on Electronic Structure - Sun, Pengju; Gao, Qilong; Liu, Junzhe; Liang, Erjun; Sun, Qiang (Frontiers in Materials, 2021)
CuSCN, as a new type of inorganic hole-transporting semiconductor with a wide-bandgap (>3.4 eV), is attracting much attention in fabrication of perovskite solar cells. In the paper, by using first principles density functional theory (DFT) and quasi-harmonic approximation (QHA) approach, we have stuided lattice dynamics and abnormal thermal expansion of the system, including α- and b-CuSCN phases. The influence of the abormal thermal expansion of the lattice on the electronic structure, especially on the band gap of the system were explored and discussed. We found that due to the shearing modes between CuS layers and the torsion modes of the Cu-N-C-S atomic chains, the α-CuSCN exhibits an anisotropic bulk negative thermal expansion (NTE). While the β-CuSCN displays strong anisotropic thermal expansion, where the lattice parameter in the c-axis direction shows a NTE due to the shearing modes between the CuS layers and the transverse vibration of the cyanide CN, but the lattice parameters in a, b-axis directions show strong positive thermal expansion. The α-CuSCN has a direct band gap, which increases slightly with increasing temperature. However, the β-CuSCN has an indirect band gap at low temperature, which converts to a direct band gap near the temperature of 375 K due to the strong positive expansion in ab plane. Our work revealed mechanisms of the abnormal thermal expansion of the two phases and a strong coupling between the anisotropic thermal expansion and the electronic structures of the systems.